Engineered Bdellovibrio bacteriovorus: A countermeasure for biofilm-induced periodontitis. (March 2022) - Tang, Ying; Huang, Qian-Xiao; Zheng, Di-Wei; Chen, Yang; Ma, Li; Huang, Cui; Zhang, Xian-Zheng
Graphical abstract: A countermeasure based on ZnO assistant Bdellovibrio (ZnO@Bdello) was reported to remove biofilm in periodontitis. ZnO@Bdello can remove Gram-negative bacteria biofilm, thereby alleviating inflammation, inhibiting bone resorption, and exhibiting an excellent effect in the treatment of periodontitis. Abstract: Periodontitis is caused by subgingival plaque biofilm mainly composed of Gram-negative bacteria, affecting human populations at a high prevalence. Antibiotics therapy is the traditional method for periodontitis, but its efficiency in removing plaque biofilm is limited. With the aim to find an effective therapeutic method to treat periodontitis, we reported a material-assistant micro-organism (MAMO) strategy to eradicate Gram-negative bacteria biofilm using ZnO nanorods engineered Bdellovibrio (ZnO@Bdello) . Bdellovibrio bacteriovorus is a natural Gram-negative bacteria predator with strong motility. ZnO nanorods are a kind of common piezoelectric material that senses mechanical pressure and produces reactive oxygen species (ROS). During the predation process of Bdellovibrio, the collision of Bdellovibrio triggered ZnO nanorods to produce ROS to enhance the removal of plaque biofilm. Both in vitro and in vivo studies showed ZnO@Bdello could remove biofilm effectively. In addition, ZnO@Bdello possessed superior competence in alleviating inflammation and inhibiting bone resorption in rats and rabbit periodontitis models. Importantly, this strategy does not induce detectable pathogen resistance and side effects.